PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT IBU DAN ANAK AMANNA DI BATURAJA - Rini Apriyani; Titin Okta (KOLEGIAL, 2023)
The results of the study obtained a multiple linear regression equation Y = 5.622 + 0.291X1 + 0.437X2. The correlation value between the variables of work motivation (X1) and work discipline (X2) on employee performance (Y) is 0.716 in the interval scale range of 0.60 â”€ 0.799 meaning that the correlation between the independent variables is work motivation (X1) and work discipline (X2 ) on the dependent variable, namely employee performance (Y) is strong. The coefficient of determination (R Square) is 0.513. This shows that the contribution of work motivation (X1) and work discipline (X2) to employee performance (Y) is 51.3% while the remaining 48.7% is influenced or varied by other variables not included in this research model. The tcount value of work motivation (X1) is 3.415 > ttable 2.00247. Ho is rejected and Ha is accepted, which means that there is an influence of work motivation (X1) on the performance of employees at the Mother and Child Hospital in Baturaja. The tcount value of work discipline (X2) is 5.550 > ttable 2.00247 Ho is rejected and Ha is accepted, which means that there is an effect of work discipline (X2) on the performance of employees at the Mother and Child Hospital in Baturaja. The value of Fcount > Ftable is 29.992 > 3.15 meaning that Ho is rejected and Ha is accepted, meaning that there is an influence of work motivation (X1) and work discipline (X2) on the performance of employees at the Mother and Child Hospital in Baturaja